2011
DOI: 10.1016/j.molcel.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Model of Mammalian BCL-2 Protein Family Interactions at the Mitochondria

Abstract: Summary During apoptosis, the BCL-2 protein family controls Mitochondrial Outer Membrane Permeabilization (MOMP), but the dynamics of this regulation remains controversial. We employed chimeric proteins composed of exogenous BH3 domains inserted into a tBID backbone that can activate the pro-apoptotic effectors BAX and BAK to permeabilize membranes without being universally sequestered by all anti-apoptotic BCL-2 proteins. We thus identified two “modes” whereby pro-survival BCL-2 proteins can block MOMP, by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
521
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 521 publications
(571 citation statements)
references
References 40 publications
28
521
7
3
Order By: Relevance
“…Anti-apoptotic Bcl-2 proteins inhibit MOMP and cell death either by directly binding BH3-only proteins or by binding activated BAX and BAK 17 . This is therapeutically important since competitive disruption of these interactionsthereby sensitizing to apoptosis-forms the mechanistic basis of BH3-mimetic action 18 .…”
Section: Apoptotic Signaling Pathwaysmentioning
confidence: 99%
“…Anti-apoptotic Bcl-2 proteins inhibit MOMP and cell death either by directly binding BH3-only proteins or by binding activated BAX and BAK 17 . This is therapeutically important since competitive disruption of these interactionsthereby sensitizing to apoptosis-forms the mechanistic basis of BH3-mimetic action 18 .…”
Section: Apoptotic Signaling Pathwaysmentioning
confidence: 99%
“…17 40 It remains unclear whether binding of BH3-only proteins to the pro-survival BCL-2-like proteins or their direct binding to BAX/BAK is more critical for the initiation of apoptosis. 37,38,41 It is, however, clear that some of the BH3-only proteins are more potent inducers of apoptosis (e.g., BIM, PUMA, tBID) than others (e.g., BAD, NOXA, BMF). Pertinently, the potent BH3-only proteins bind avidly to all prosurvival BCL-2 family members and can also engage BAX/ BAK, whereas the less potent ones have more select binding specificities for the pro-survival BCL-2 family members and reportedly do not bind to BAX or BAK.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…Genetic 2,17 as well as biochemical experiments [18][19][20][21][22][23] have indicated that the BH3-only proteins BIM, PUMA, a protease generated BID fragment (tBID), and, in some studies, NOXA can directly bind and activate BAK and/or BAX. To counteract these effects, antiapoptotic BCL2 family members such as BCL2, BCLX L and MCL1 bind and neutralize activated BAX and/or BAK 2,6,16,24 as well as activated or overexpressed BH3-only family members, [25][26][27][28][29][30] thereby preserving MOM integrity.…”
mentioning
confidence: 99%